Sublethal heat treatment of hepatocellular carcinoma promotes intrahepatic metastasis and stemness in a VEGFR1-dependent manner. (28th September 2019) - Tan, Li; Chen, Shuling; Wei, Guangyan; Li, Yue; Liao, Junbin; Jin, Huilin; Zou, Ying; Huang, Manling; Peng, Zhenwei; Guo, Yu; Peng, Sui; Xu, Lixia; et al.
Abstract: Incomplete radiofrequency ablation (RFA) of hepatocellular carcinoma (HCC) could initiate malignant transition. Patient-derived xenograft (PDX) mice model was established to investigate the effect of VEGF pathway in incomplete RFA of HCC with high fidelity. Cancer stem cell markers and metastatic markers were increased after incomplete RFA, with increased VEGFR1 and decreased VEGFR2 expression. In vitro experiments revealed sublethal heat treatment promoted migration ability of HepG2, HCCLM3, and SMMC7721 cells, which coincided with enhanced ability of sphere formation and up-regulation of VEGFR1, CD133, CD44, and EpCAM. Moreover, HCC cells secreted more VEGF after heat-treatment. VEGF promoted migration and enhanced stemness of HCC cells, which could not be suppressed by VEGFR2 inhibitor. PIGF, the ligand of VEGFR1, significantly increased migration and stemness of HCC cells. Blocking VEGFR1 reduced heat-induced enhancement of migration and stemness, whereas inhibition of VEGFR2 could not. In conclusion, VEGFR1 plays a critical role in sublethal heat treatment-induced enhancement of migration and stemness in HCC, suggesting that VEGFR1 may serve as a potential and promising therapeutic target for preventing recurrence after RFA. Highlights: Incomplete radiofrequency ablation of HCC patient-derived xenograft mice model was established for the first time. VEGF pathway contributes to the RFA-related tumor metastasis and cancer stemness. VEGFR1, instead of VEGFR2, mediates the migration and cancer stemness enhancement after sublethal heat treatment.